THE MULTILATERAL STRUCTURES AND LEGAL FOUNDATIONS OF RUSSIA’S SECURITY POLICY IN CENTRAL ASIA - CHOTAEV, Zakir (CENTRAL ASIA AND THE CAUCASUS, 2006)
In 1991, when the Soviet Union ceased to exist and when Russia lost the larger part of its economic, political, and military potential, it had to build up its foreign policy under the new conditions from scratch. In the next 15 years, its policy went through several development stages, each of them marked by revised foreign policy trends and approaches.1 At the first stage, Moscow concentrated on broader relations with the West and, for that reason, temporarily moved away from the former Union republics. However, as soon as the West and the countries of the region increased their pressure on the post-Soviet expanse, the Kremlin promptly revised its foreign policy ideas to turn the limelight on the CIS. In 1993, the then RF Foreign Minister Andrey Kozyrev elaborated a new foreign policy conception for the Russian Federation that, together with continued relations with the U.S. and Western Europe, spoke about developing cooperation within the CIS and protecting Russia’s interests and the rights of the Russian-speaking minorities, as well as conflict settling across the post-Soviet expanse, which was described as a sphere of Moscow’s special responsibil-ity.2 Russia’s military doctrine likewise dwelt on the key military-strategic aspects of Russia’s polices in the Near Abroad. Meanwhile, the socioeconomic situation in the post-Soviet expanse was rapidly worsening; the area was swept by destabilization caused by separatism and ethnic strife. This, in turn, ignited armed conflicts. Having assumed responsibility for conflict settlement and stronger security and peace in the region, Moscow envisaged the possibility of using force in its new military doctrine. In view of NATO’s eastward movement and stronger Western and regional pressure, the Russian leaders had to take urgent measures to limit this influence and keep foreign forces at bay in the post-Soviet expanse. While defending its interests, Moscow renounced its pledge not to be the first to use nuclear weapons to protect its territory as well as that of its allies against external enemies. It was obviously an effort to “tie” the militarily and economically weak CIS members to it by strengthening joint security. The outside world interpreted Russia’s new foreign policy course in the CIS as Moscow’s neo-imperialist ambitions and its desire to preserve its military presence and political influence in the region.3